Feasibility of Sago bioethanol liquid waste as a feedstock for laccase production in recombinant Pichia pastoris - Farah Wahida, Mamat; Nurashikin, Suhaili; Ngieng, Ngui Sing; Micky, Vincent; Dayang Salwani, Awang Adeni (World Research Associations, 2021)
The use of waste stream generated upon the production of bioethanol from sago fibre has not been a major focus in the literature thus far. This study explores the feasibility of utilising the liquid waste generated following the production of bioethanol from sago fibre as a feedstock for the production of recombinant laccase in Pichia pastoris GS115. Characterisation of the sago bioethanol liquid waste (SBLW) indicated that glycerol was the main constituent along with glucose and lactic acid. Our results showed that P. pastoris GS115 growth was generally feasible when SBLW was used as a feedstock irrespective of its concentration. The expression of laccase reached the highest in fermentations that employed 40% (v/v) SBLW, whilst higher concentrations of SBLW resulted in the reduction of the laccase activity. The highest laccase activity achieved using 40% (v/v) SBLW represented 73% of that obtained using the standard synthetic medium. Further enhancement of maximum biomass concentration by 1.2-fold and laccase titre by 1.5-fold was achieved when the 40% (v/v) SBLW was supplemented with 1.0% (w/v) yeast extract. This work gives useful insights into the promising applications of SBLW as an inexpensive and sustainable feedstock for the production of industrial biocatalysts.